Cork and Alcoholic Beverages - Maga, Joseph A; Puech, Jean-Louis (Food Reviews International, 2005)
For centuries, cork has been the stopper of choice for various alcoholic beverages. In this review, cork history, sources, production, physical properties, composition, off-flavors, and alternatives to cork stoppers are discussed.
doi: 10.1081/FRI-200040593
Keywords: Alternatives; composition; production; Properties; stoppers; Taint